No music, no life? a historical study of PULP Magazine - Anonuevo, Klara Iskra M. 1986-
"This historical study traced how PULP Magazine developed since its inception in 1999 up to the publication of its sixth anniversary issue in December 2005. The magazine was viewed as on open system, and this study evaluated how the magazine influenced and was influenced by its environment, the Philippine society. This study also sought to explain and analyze other aspects of the magazine, like its target audience and its organizational structure, and how these affected the history of the magazine. The researcher interviewed people significant to the development of tha magazine and found out that the magazine has survived mainly because it has learned to adapt to changes that occurred both internally and externally."